Tracing Surrogates for Enteric Pathogens Inoculated on Hide through the Beef Harvesting Process - Villarreal-Silva, Mariana; Genho, Daniel P.; Ilhak, Irfan; Lucia, Lisa M.; Dickson, James S.; Gehring, Kerri B.; Castillo, Alejandro (Int Assoc Food Protection, 2016)
Multiple antimicrobial interventions have been validated for use during the beef postharvesting process. However, little has been done to determine the impact of the postharvest environment on pathogen contamination In this study, surrogate microorganisms were used to simulate pathogen cross-contamination through the postharvest environment at three different abattoirs. At each abattoir, the brisket areas of 13 hide-on carcasses were inoculated after stunning, with a gelatin slurry containing a cocktail (similar to 7 log CFU/ml) of fluorescent Escherichia coli biotype I. These microorganisms are approved as surrogates for E. coli O157:H7 and Salmonella. From these carcasses, samples (300 cm(2)) were taken at different stages during the harvesting process: after hide opening, prior to evisceration, after evisceration, after splitting, and after final intervention. The carcass (noninoculated) immediately following (adjacent to) each hide-inoculated carcass was also tested to determine cross contamination. Environmental (floor, walls, air) and personal garment (gloves, boots, aprons) samples were collected. Other sampled equipment included knives, meat hooks, hide pullers, and splitting saws. Results demonstrated that cross-contamination occurred between the inoculated hide and the carcass and also by transfer of microorganisms to the adjacent, noninoculated carcasses. Microbial transfer also occurred from hides or carcasses to the environment, personal garments, and equipment. Counts of the surrogate bacteria used were higher in equipment samples (15%) than in environment samples (10%). Personal garments had the lowest occurrence of cross-contamination (7%). For all abattoirs, surrogates were undetected on the carcass (<1.4 log CFU/300cm(2)) after the final intervention stage. This study confirms the importance of following adequate procedures for carcass dressing and highlights an adequate hide opening procedure as a crucial step to prevent carcass contamination.
Keywords: Beef harvest; Escherichia coli O157:H7; Salmonella; Surrogate microorganism